Signaling Can Be Uncoupled from Imaging of the Somatostatin Receptor Type 2 - Lin Han; Dan Yang; Vikas Kundra (Molecular Imaging)
Endogenous and exogenous somatostatin receptors are commonly targeted for imaging using radiopharmaceutical analogues of somatostatin. Ligand binding activates receptor-mediated signaling. We assessed whether somatostatin receptor type 2A (SSTR2A) imaging can be uncoupled from signal transduction. In both human fibrosarcoma (HT1080) and human embryonic kidney (HEK293) cells, reverse transcriptase–polymerase chain reaction and enzyme-linked immunosorbent assay found similar levels of expression of hemagglutinin A tagged SSTR2A (HA-SSTR2A) or the same fusion protein with a deletion of the C-terminus beyond amino acid 314 (HA-SSTR2Δ314). Scatchard analysis demonstrated similar degrees of ligand binding by the wild-type or mutant receptor to 111 In-octreotide in both cell pairs. Cyclic guanosine monophosphate (cGMP) production and inhibition of forskolin-induced cylic adenosine monophosphate (cAMP) production were evaluated at the signaling level, and growth inhibition was evaluated at the cellular level before and after stimulation. Unlike wild-type receptor, HA-SSTR2Δ314 was deficient in inhibiting forskolin-induced cAMP production ( p < .05) and in inciting cGMP ( p < .05) production; furthermore, at the cellular level, HA-SSTR2Δ314 was deficient in inhibiting cell proliferation ( p < .05). Yet tumors expressing HA-SSTR2Δ314 could be imaged in vivo. Thus, in vivo imaging of SSTR2 can be uncoupled from cAMP and cGMP signaling as well as growth inhibition.